Gloss to the judgement of the Supreme Administrative Court of 8th June 2016, I FSK 293/15 - Mateusz Niemiec (Prawo Budżetowe Państwa i Samorządu)
This study is an approving comment to the decision of the Supreme Administrative Court of 8th June, 2016, case No. I FSK 293/15. The author discusses problems relating to the legal features and the consequences of removing an active VAT taxpayer from the register. He is focused on the removal which is caused by the taxpayer’s non-reporting about the cessation of activities subject to taxation. The study also emphasizes the impact of the commented decision on the development of the judicial line within the scope of the discussed legal issue.